Using Mathematical Model in Audit of Compliance with the Principle of Continuity of Company Activities - Selishchev, S. V. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The article’s objective is to study and systematize the existing methods to assess the risk of termination of company activities, and to develop a methodology for applications of factor models in assessment of this risk. Criteria to be met by the method selected for audit are highlighted. The extensive review of the most widespread methods for predicting the financial performance at company level is made: computation of current ratio, computation of acid text ratio, Beaver model, two-factor model of Altman, five-factor model of Altman, Springate model. The study aimed at further development and adaptation of the existing mathematical models for audit of compliance with the principle of continuity of company activities is made. The review of the above mentioned methods and analysis of their applications in the procedures involved in assessing the risk of inadequate use of the assumption on the continuity of company activities in preparing financial reports by company managers allows for the conclusion that the best way to obtain auditor evidence based on mathematical coefficients reflecting the declining economic performance of a company is to apply the methods for computation of current ratio and acid text ratio, and Springate model.